2009
DOI: 10.4049/jimmunol.0900132
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Conjugation of Open Reading Frame F DNA Vaccine Leads to Enhanced Cell-Mediated Immune Response and Induces Protection against Both Antimony-Susceptible and -Resistant Strains ofLeishmania donovani

Abstract: Resistance of Leishmania donovani to sodium antimony gluconate has become a critical issue in the current, prolonged epidemic in India. Hence, there is an urgent need for a vaccine that is protective against both antimony-susceptible and -resistant strains of L. donovani. The multigene LD1 locus located on chromosome 35 of Leishmania is amplified in ∼15% of the isolates examined. The open reading frame F (ORFF), a potential vaccine candidate against visceral leishmaniasis, is part of the multigene LD1 locus. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 68 publications
4
17
0
Order By: Relevance
“…The modulated immune response indicated that the expressed HSP65 protein had a higher rate of intracellular degradation in a proteasome pathway because of the addition of UbGR. Our result is consistent with the Sharma A's report [28], which showed that immunization with DNA vaccine encoding ORFF fused to Ub induced higher IFN-γ, stronger Th 1 responses than those of unmodified vaccines. However, no effect was seen for another antigen PyCSP using the same targeting strategies.…”
Section: Discussionsupporting
confidence: 83%
“…The modulated immune response indicated that the expressed HSP65 protein had a higher rate of intracellular degradation in a proteasome pathway because of the addition of UbGR. Our result is consistent with the Sharma A's report [28], which showed that immunization with DNA vaccine encoding ORFF fused to Ub induced higher IFN-γ, stronger Th 1 responses than those of unmodified vaccines. However, no effect was seen for another antigen PyCSP using the same targeting strategies.…”
Section: Discussionsupporting
confidence: 83%
“…Promotion of the Th1 response over that of Th2 is associated with control of disease in case of cutaneous leishmaniasis. Although such clear polarization is not the case in visceral leishmaniasis, the Th1 response correlates with resistance to infection [32]. In this light, the modulation of proinflammatory over anti-inflammatory cytokines by PTP inhibitors might favor a better control over infection in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Carter et al (71) and Sharma and Madhubala (72) vaccinated mice with pVAXγGCS (gamma-glutamyl cysteine synthetase) and UBQ-ORFF, respectively, which resulted in a protective response to increased levels of IL-12 and IFN-γ and the lower levels of IL-4 and IL-10 confirming Th1-type response.…”
Section: Molecular Approaches To Leishmania Vaccine Developmentmentioning
confidence: 99%